Academic Oral Presentation Anxiety and Coping Strategies among Non-English Major Students at the University of Bengkulu - Yusri Fajri Annur; Wisma Yunita (JEELS (Journal of English Education and Linguistics Studies), 2025)
The aim of this study was to review the self-perceived oral presentation anxiety and coping strategies of non-English majors of the University of Bengkulu. The research used a descriptive quantitative approach in sampling the 130 participants to gather information through the Personal Report of Public Speaking Anxiety (PRPSA) and Oral Communication Strategy Inventory (OCSI). Students reported a moderate anxiousness, which was associated with language and assessment. Use of social-affective measures, such as self-talk and relaxation, was most common in students and then by fluency-oriented measures. The results of One-Way ANOVA indicated that the difference in the use of strategies by level of anxiety was significant. Social-affective strategies and fluency-specific strategies were more common among high-anxiety students (F=26.70, p <.001; F=11.94, p <.001). Conversely, message simplification was popular among the moderate-anxiety students (F=15.78, p <.001). What the study determines is that there are special strategies, such as specially designed interventions, such as message construction workshops, fluency training, and relaxation methods, that can facilitate the quality of presentation. Such results shed light on the strategies that the non-English majors adopted to overcome presentation anxiety and offer ways in which the EFL learners can reduce the latter.